Dissection of Drosophila Adult Brains for Patch-Clamping Neurons - Fernandez Chiappe, Florencia (2022)
The brain of adult flies (Drosophila melanogaster) has been studied in detail from several perspectives, including the anatomical and molecular characterization of hundreds of neuronal types. However, information regarding the electrophysiological properties of most neuronal types is lacking. This protocol provides detailed information on how to dissect the brain of adult flies to produce an ex vivo preparation in which central neurons can be patch-clamped. Immobilizing fresh and tiny tissues, such as fly brains, to perform successful patch-clamp recordings is a critical step; here, we explain how this can be achieved using cyanoacrylate glue.